Discourse on Relations Between Indonesia and Papua: Content Analysis of History Textbook of 2013 Curriculum - Handoko, Susanto T; Wasino, Wasino (History Department, Semarang State University and Historian Society of Indonesia, 2020)
This research is motivated by the existence of a national identity crisis in Indonesian society, especially in young people or students. This research aims to analyze the discourse on relations between Indonesia and Papua found in a history textbook for senior high school of 2013 curriculum. Through this research, an understanding of how the state reconstructs national identity (Indonesian-ness) and local identity (Papuan-ness) in a history textbook for senior high school used by senior high school students in Jayapura City. The research method used is the qualitative method, which focuses on the content analysis of the history textbook. This analysis will focus on the relations between Indonesia and Papua. The meaning process was conducted using two concepts, namely Indonesian-ness and Papuan-ness. Then, those two concepts were represented in three themes: ethnic nationalism, nationalism, and national integration. The results of the research showed that the discourse on national identity (Indonesian-ness) and local identity (Papuan-ness) was a product of the governmentÃ¢â‚¬â„¢s political policies in education, namely ideology and state identity.Ã‚Â Penelitian ini dilatarbelakangi oleh adanya krisis identitas nasional di masyarakat Indonesia, terutama pada kaum muda atau pelajar. Penelitian ini bertujuan untuk menganalisis wacana tentang hubungan Indonesia dan Papua yang ditemukan dalam buku teks sejarah untuk kurikulum SMA 2013. Melalui penelitian ini, pemahaman tentang bagaimana negara merekonstruksi identitas nasional dan identitas lokal dalam buku teks sejarah untuk SMA yang digunakan oleh siswa SMA di Kota Jayapura. Metode penelitian yang digunakan adalah metode kualitatif, yang berfokus pada analisis isi buku teks sejarah. Analisis ini akan fokus pada hubungan antara Indonesia dan Papua. Proses pemaknaan dilakukan dengan menggunakan dua konsep, yaitu keindonesiaan dan ke-Papua-an. Kemudian, kedua konsep tersebut diwakili dalam tiga tema: nasionalisme etnis, nasionalisme, dan integrasi nasional. Hasil penelitian menunjukkan bahwa wacana tentang identitas nasional dan identitas lokal adalah produk kebijakan politik pemerintah dalam pendidikan, yaitu ideologi dan identitas negara.